Comparison of the diagnostic efficacy between urease and histopathological tests in H. pylori (Research, Society and Development, 2024)
• pylori infection is globally prevalent, varying by age, geographic location, and socioeconomic status. In Brazil, it is estimated that it affects around 70% of the population, increasing with age and being lower in the white population, regardless of sex. The objective of this study was to compare the results of histopathological and urease tests in patients, highlighting a higher positivity in the former (42%) compared to previous studies. The analysis of age groups revealed a higher prevalence of positive H. pylori in patients between 30-39 years old, differing from other studies. Regarding gender, a higher incidence was observed in males (47%), similar to previous studies. Dyspeptic symptoms were observed in 48% of patients, but were not directly correlated with H. pylori positivity. Regarding clinical variables, the majority of patients did not have drug allergies (76%) or significant comorbidities, and among those who had comorbidities, systemic arterial hypertension was the most prevalent (73.7%). Clinical tests, especially urease and histopathology, were compared, showing similar results, although the urease test has been suggested as useful in ruling out infection when negative. It is concluded that the combination of both methods can be beneficial. This study contributes to the understanding of the prevalence of H. pylori, highlighting the importance of joint assessment of diagnostic tests and the need for more research on correlations with specific clinical variables.